Practitioner's view of barriers to software outsourcing partnership formation: An empirical exploration. Issue 5 (2nd December 2019) - Ali, Sikandar; Li, Hongqi; Khan, Siffat Ullah; Abrar, Muhammad Faisal; Zhao, Yanhong
Abstract: Software Outsourcing Partnership (SOP) is considered as a kind of risk and reward sharing client‐vendor relationship. Generally, a fruitful outsourcing association might be converted to an outsourcing partnership. The objective of this research is to identify and analyse barriers that are hurdles to vendors in renewing or promoting their ongoing client‐vendor relationship to outsourcing partnership. A questionnaire survey based on the findings of Systematic Literature Review (SLR) was performed with 50 experts. The study identifies five critical barriers such as "insufficient quality of technical capability, " "poor infrastructure, " "poor quality of service, " "communication gap and poor coordination, " and "relational risk." The results indicate that barriers' insufficient quality of technical capability, poor infrastructure, and poor quality of service were common in four types of experts while insufficient quality of technical capability is common in three levels of experts. Furthermore, barriers were classified based on their criticality from client‐vendor perspective. The results of Spearman correlation test (rs = 0.714 and ρ = 0.000) confirmed that the participant strongly agrees with the outcomes of the SLR. The results suggest that for successful renewal or promotion of their existing outsourcing association, vendor organizations should address all the identified barriers in general and the most common barriers in particular.